Hubungan Luar Negeri Indonesia melalui Otonomi Daerah: Studi Evaluasi Sister city Medan Dengan Penang tahun 2010-2022 - Addarsyah Dhia Putra; Sidik Jatmika (Program Studi Ilmu Pemerintahan Universitas Islam Raden Rahmat Malang, 2023)
Abstract The autonomous cooperation policy between the cities of Medan and Penang was established in 1984. Since its inception, this cooperation has resulted in various mutually beneficial cooperation for both parties involved. The purpose of this study is to assess previous examples of cooperation to identify shortcomings in the programs that have been implemented. By addressing these shortcomings, future efforts can aim to limit mistakes and reduce gaps in benefits achieved. This study utilized a qualitative research approach and used Publish or Perish 8 software to identify relevant data sources for the purpose of this paper. International cooperation theory serves as a framework to assess the effectiveness of existing cooperation efforts. The findings of this research will shed light on the extent of the collaboration that has been developed such as modifying the way sister cities are around as one of the foundations in evaluating the cooperation that has been established and then analyzing and interpreting these findings in the discussion section.